Plant stress response and adaptation via anthocyanins: A review - Zhe Li; Golam Jalal Ahammed (Plant Stress, 2023)
Global climate change has caused an increase in extreme weather events and subjected plants to a variety of abiotic stress. Plants being rooted in the soil are unable to avoid abiotic stress by relocation. Therefore, plants have evolved sophisticated mechanisms to cope with abiotic stress that negatively affects photosynthesis, respiration, cell water potential, and eventually normal growth and development. Anthocyanins, a kind of flavonoid, are water-soluble natural pigments of various colors in plants, which can safeguard plants from a wide range of environmental stress. Anthocyanins have antioxidant functions and play an indispensable role in scavenging reactive oxygen species (ROS). Moreover, anthocyanins act as ''sunscreens'' and form chelates with metals/metalloids to alleviate metal stress. Nonetheless, the biosynthesis and stability of anthocyanins are affected by a variety of external factors. Here, we review the regulatory mechanisms of anthocyanin synthesis, the effects of environmental factors on anthocyanin production, and the role of anthocyanins in the response of plants to environmental stress including drought, salt stress, high light intensity, ultraviolet rays, heavy metals, and low temperature. Considering the important role of anthocyanins in stress tolerance, increasing anthocyanin content by manipulating regulatory genes can potentially be useful to improve plant stress resistance, which are putative solutions for resilience to extreme environments today and in the future.